Letrozole Versus Clomiphene Citrate and Natural Cycle: Endometrial Receptivity During Implantation Window in Women With Polycystic Ovary Syndrome - Wang, Li; Lv, Shulan; Li, Fen; Bai, E.; Yang, Xiaofeng (Frontiers in Endocrinology, 2021)
Objective: Numerous studies have reported on ovulation and pregnancy rates in patients with polycystic ovary syndrome (PCOS). However, relevant data of endometrial receptivity are limited. This study was conducted to compare endometrial receptivity during implantation window among letrozole (LE), clomiphene citrate (CC) and natural cycle, and to assess the predictive value for pregnancy of observed indicators. Methods: This randomized controlled trial study enrolled 270 patients with PCOS. Patients were given LE (n=90) at a dose of 2.5mg/day or CC (n=90) at a dose of 50 mg/day on cycle days 5–9 for ovulation induction. Patients in natural cycle group (n=90) did not receive any drug for ovulation induction. Endometrial ultrasonic parameters, integrin αvβ3 and vascular endothelial growth factor (VEGF) concentrations in uterine secretion were detected during implantation window. The endometrial receptivity, ovulation rate, pregnancy rates and predictive value of observed indicators for pregnancy were analyzed. Results: The successful ovulation rate did not differ between LE group and CC group (P>0.05). Endometrial ultrasonic parameters [endometrial thickness (ET), endometrial volume (EV), vascularization index (VI), flow index (FI), vascularization flow index (VFI)], integrin αvβ3 and VEGF concentrations in uterine fluid were significantly higher in LE group compared with CC group and natural cycle group (P<0.05). The clinical pregnancy and ongoing pregnancy rates of LE group were significantly higher than in CC group (P<0.05). Endometrial ultrasonic parameters (VI, FI and VFI), integrin αvβ3 and VEGF concentrations in uterine fluid of all pregnancy groups were significantly higher compared with no pregnancy group (P<0.05), and the above parameters in ongoing pregnancy were significantly higher than in biochemical pregnancy (P<0.05). The endometrial FI during implantation window had the highest predictive value for pregnancy (AUC=0.889). The integrin αvβ3 in uterine fluid had better predictive value (AUC=0.876) than VEGF. Conclusions: Endometrial receptivity during implantation window of LE is superior to CC in PCOS women, which may be related to higher clinical pregnancy and ongoing pregnancy rates. Endometrial FI examined by 3-D power Doppler, and integrin αvβ3 in uterine secretion during implantation window could be preferable non-invasive predictor markers for pregnancy.